Evaluation of ISO 11785 low-frequency radio identification devices and the characterization of electromagnetic interference in practical cattle management scenarios - Ryan, Sarah Ellen (Kansas State University, 2008)
Low-frequency (LF) radio frequency identification (RFID) transponders (n = 1,993) representing both full-duplex and half duplex air interface technologies were evaluated. Transponders representing five manufacturers and seven types were evaluated for read distance (RD), resonance frequency (RF) and voltage response (VR). LF RFID transceivers (n = 24) were also evaluated for performance and variance as tested by read distance. Transponders were sorted into four categories based on RD performance on three transceivers, “Top 25%,” “Middle 50%,” “Bottom 25%,” and “No Read.” These categories were used for evaluation of transponders and transceivers in experiments one and two, respectively. In experiment one, the mean RF of the “Top 25%” transponders were closer to 134.2 kHz (P < 0.05) within a transponder type (TT). TT and mean RD performance category interacted to affect the VR of transponders (P < 0.05); transponders with lower VR tended to have longer RD within a TT. In experiment two, sixty transponders from the “Middle 50%” were used to evaluate transceivers. Transceivers represented five manufacturers and five transceivers per manufacturer; one transceiver was eliminated from testing due to mechanical problems. There was a significant interaction (P < 0.0001) for TT and transceiver manufacturer. This indicated that transceiver performance was greatly dependant on TT being interrogated. TT and transceiver manufacturer interacted to affect RD variance (P < 0.05) demonstrating that transceiver RD will vary depending on TT being interrogated. In the final study, electromagnetic interference (EMI) was evaluated in fourteen livestock auction markets, four feedlots and five cattle abattoirs. The presence of EMI is known to impair the performance of RFID equipment. However, this phenomenon in livestock management settings has not been quantified in the scientific literature. EMI (134.2 + 25 kHz) was observed in all abattoirs. However, the extent and duration of EMI varied depending on individual abattoir. The processing, load and unload areas were evaluated in commercial feedlots. The most EMI was observed in the processing area. Finally, EMI was observed at the sale ring exit at two livestock auction markets. EMI exists in livestock management settings and may negatively impact the performance of LF RFID.
Keywords: Radio frequency identification; Animal identification; Electromagnetic interference; Cattle management; Agriculture, Animal Culture and Nutrition (0475)